HUBUNGAN POLA MAKAN DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI DI SMA NEGERI KATALA HAMU LINGU - Erli Rosdini Hona Nalu; Raden Maria Veronika Widiatrilupi (Journal of Innovative and Creativity (Joecy), 2026)
Anemia continues to be a major public health concern among adolescent girls, particularly in developing countries such as Indonesia. Although inadequate dietary intake, especially insufficient consumption of iron-rich foods, is frequently considered a contributing factor, its association with anemia remains inconsistent across different populations. This study was conducted to examine the relationship between dietary patterns and anemia prevalence among female students at SMA Negeri Katala Hamu Lingu. A quantitative research design with a cross-sectional and descriptive correlational approach was applied. The study involved 87 adolescent girls who were recruited through a total sampling technique. Dietary pattern served as the independent variable, whereas anemia status was treated as the dependent variable. Data collection was carried out using a dietary pattern questionnaire and hemoglobin (Hb) measurements, followed by statistical analysis using the Chi-Square test at a significance level of 5%. The findings revealed that 47 participants (54%) demonstrated healthy dietary patterns, while 40 participants (46%) exhibited less favorable dietary habits. Regarding anemia status, 50 respondents (57.5%) had normal hemoglobin levels, whereas 37 respondents (42.5%) were diagnosed with anemia. The Chi-Square analysis generated a p-value of 0.387 (p > 0.05), indicating that dietary patterns were not significantly associated with anemia among the participants. These results suggest that factors beyond dietary habits may play a more substantial role in the development of anemia, including nutritional status, menstrual characteristics, adherence to iron supplementation, socioeconomic conditions, and other health-related determinants affecting adolescent girls.